The Journey Of Ummah - Roihan, Muhammad Irham; Munawwaroh, Nafiatul (Universitas Islam Indonesia, 2017)
Title book : Dinamika Sejarah Umat Islam Indonesia(The Dynamics of History of Islamic Society in Indonesia)Writer : KuntowijoyoPublisher : Mata Bangsa, YogyakartaYear Publishing : First edition : June 2017Pages : i-x + 203 All human being is facing a “historical process.” In the process of history, many dynamics have occurred in both the ‹in concreto› and ‹in abstracto› worlds. Indonesian Muslims have also undergone the same thing, and in this important work, Kuntowijoyo attempts to map out the historical journey of Indonesian Muslims, using structural and cultural analysis that can explain the various essential roles of in this country.The development of Islam in Indonesia gives the massive impact on the Indonesian history. The Dynamics of the History of Islamic Society in Indonesia is one of important works of Kuntowijoyo that was first published in 1985 covering his articles he wrote during 1984 - 1985 and then republished in 2017. This book portrays the development of Islamic society in Indonesia with a unique point of view. The author used sociocultural and socio-economic perspective to analyze the history of Islamic civilization from the early stage until the industrialization era, which rarely becomes the concern of intellectuals in Indonesia.